Implementation of a program to support direct support professionals to promote a healthy lifestyle for people with moderate to profound intellectual disabilities - A. Overwijk; T. I. M. Hilgenkamp; C. P. van der Schans; W. P. Krijnen; K. Vlot-van Anrooij; A. A. J. van der Putten; A. Waninge (BMC, 2022)
Abstract Background There is a lack of theory-based interventions for direct support professionals (DSPs) to support a healthy lifestyle for people with moderate to profound intellectual disabilities (ID) despite their major role in this. This study aims to evaluate the preparation, implementation, and preliminary outcomes of a theory-based training and education program for DSPs to learn how to support these individuals. Methods The program consisting of e-learning, three in-person sessions, and three assignments was implemented. The implementation process was evaluated with a mixed method design with the following components: preparation phase, implementation phase, and the outcomes. These components were measured with project notes, questionnaires, interviews, reflections, assignments, food diaries, Actigraph/Actiwatch, and an inventory of daily activities. Results Regarding the preparation phase, enough potential participants met the inclusion criteria and the time to recruit the participants was 9 months. The program was implemented in four (residential) facilities and involved individuals with moderate to profound ID (n = 24) and DSPs (n = 32). The e-learning was completed by 81% of the DSPs, 72-88% attended the in-person sessions, and 34-47% completed the assignments. Overall, the fidelity of the program was good. DSPs would recommend the program, although they were either negative or positive about the time investment. Mutual agreement on expectations were important for the acceptability and suitability of the program. For the outcomes, the goals of the program were achieved, and the attitudes of DSPs towards a healthy lifestyle were improved after 3 months of the program (nutrition: p = < 0.01; physical activity: p = 0.04). A statistically significant improvement was found for food intake of people with ID (p = 0.047); for physical activity, no statistically significant differences were determined. Conclusions The theory-based program consisting of a training and education section for DSPs to support a healthy lifestyle for people with moderate to profound ID was feasible to implement and, despite some barriers regarding time capacity and mutual expectations, it delivered positive changes in both persons with moderate to profound ID and DSPs. Thus, the program is a promising intervention to support DSPs.